Case Report: Novel findings of larotrectinib in children with NTRK-rearranged spindle cell tumor - Wu, Linnan; Xie, Weiji; Wang, Juan; Lu, Suying; Zhang, Yizhuo; Huang, Junting (Frontiers in Oncology, 2025)
Neurotrophic tropomyosin receptor kinase (NTRK)-rearranged spindle cell tumors are often resistant to chemotherapy and radiotherapy. Fortunately, they are sensitive to targeted therapy of tropomyosin receptor kinase (TRK) inhibitors. However, the data on larotrectinib in Chinese children with NTRK-rearranged spindle cell tumor are still scarce. We reported 4 children with TRK fusion-positive solid tumors received larotrectinib in different clinical scenarios, including second-line treatment after progressive disease (patient #1), relapse after resection (patients #2 and #3), and metastatic disease (patient #4) and all of them benefited from the treatment. The patients harbored different TRK fusion genes (patient #1: TP53-NTRK1; #2: TPM3-NTRK1; #3: TPM3-NTRK1, DCST1-NTRK1, ZBTB7B-NTRK1, and NTRK1-DCST2; #4: LMNA-NTRK1). Our study provides new insights into the biology and management of NTRK-rearranged spindle cell tumors, contributing to the expanding evidence supporting the use of TRK inhibitors in these tumors. Further studies are needed to validate our findings and to explore the potential of second-generation TRK inhibitors in overcoming resistance.